Atypical presentation and management of Persistent Neonatal Hypoglycemia - Rakshak, Balay Sai; Kumar Thapar, Rajeev; Mishra, Aditi; Chhillar Vij, Poonam (Journal of Neonatal Surgery, 2025)
Background: Neonatal hypoglycemia is a common metabolic disorder that manifests with non-specific clinical symptoms like poor feeding, irritability, apnoea, and seizures or may present asymptomatically. Screening of at-risk neonates; small for gestational age (SGA), preterm and infants of diabetic mothers (IDM)—is crucial for early diagnosis and prevention of long term sequalae. The Pediatric Endocrine Society defines neonatal hypoglycemia as blood glucose levels less than 50 mg/dL within the first 48 hours postnatally. Persistent hypoglycemia, characterized by the necessity for intravenous dextrose beyond this timeframe, mandates comprehensive critical sample analysis to elucidate its aetiology. Clinical Description: A late preterm, SGA male infant had persistent hypoglycaemia despite normal insulin levels and the absence of identifiable sepsis, metabolic or endocrine disorders. Initial management entailed intravenous dextrose along with hydrocortisone; however, due to the persistence of hypoglycaemia and normal critical sample results neonate was managed effectively with an alternative drug. Management & Outcome: Oral diazoxide was initiated at a dosage of 5 mg/kg/day, leading to the attainment of euglycemia within five days. The infant was subsequently discharged with instructions for continued medication and monitoring, ultimately tapering off diazoxide after four weeks while maintaining normal growth and developmental parameters. Conclusion: Persistent hypoglycemia in preterm SGA infants was effectively managed with diazoxide, although the precise mechanisms underlying this phenomenon remains to be elucidated. Continued research is needed to clarify the pathophysiology and therapeutic implications of this treatment modality.